Quantifying the dynamic processes of soil erosion and lake sediment deposition in the Holocene in China. (15th March 2023) - Hongfei Zhao,; Lin, Yunhong; Zhou, Jie; Sun, Qianli; Yang, Linhai; Delang, Claudio O.; He, Hongming
Abstract: The Holocene lake sediment records are critical indicators of past global change studies. This study attempts to reconstruct soil erosion rates (SERs) quantitatively based on lake sediment records from 35 lakes in China. Environmental sequences, e.g., precipitation, vegetation and human activity, were reconstructed and used to identify the dynamic processes of soil erosion based on the General Additive Model (GAM). The findings were as follows. First, drivers of soil erosion in lake basins in different sub-regions of China differed markedly due to the evolution of different monsoon systems and regional environments. Second, influenced by the evolution of different monsoon systems and regional environments, soil erosion of the Holocene showed different evolutionary processes in China. For example, SERs gradually increased in the northwestern arid zone and remained relatively stable in the monsoon zone until 2.0 ka (1 ka = 1000 calibrated a B.P.). Third, human activity played a more important role in soil erosion in all sub-regions during the Holocene. Human activities through vegetation/land-use change have led to rapid enhancement of soil erosion in the north, south, and southwest China since 2.0 ka, especially in the last 1000 years. This study contributes to our understanding of the evolution of soil erosion under different climate systems in China. Highlights: Holocene soil erosion rates were reconstructed quantitatively based on lake sediment records. Drivers of soil erosion differed markedly due to the evolution of different monsoon systems in China. Human activities have led to rapid enhancement of soil erosion since last 2000 years.